Analisis Sistem Pengendalian Internal Kas Kecil (Petty Cash) Pada Suku Dinas Kebudayaan Kota Adminitrasi Jakarta Timur - Fifi Rochaniatul Hasanah; Amin Setio Lestiningsih; Intan Kusuma Dewi (Institut Nalanda, 2024)
Considering current developments, business entities are required to manage activities within their companies while at the same time being able to overcome problems that arise in the field of controlling their assets. Suku Dinas Kebudayaan Kota Adminitrasi Jakarta Timur is an agency that operates in the field of employment activities by carrying out programs such as craftsmanship development, craftsmanship development in public areas, carrying out crafts training, such as mursik art, fine art and dance art, as well as the City Employment Service Surkur. Suku Dinas Kebudayaan Kota Adminitrasi Jakarta Timur administration is also active in organizing events at the city level by providing entertainment in the form of selected arts such as regional dances, mursik tanjidor. This research aims to find out whether the internal control system for petty cash is running in accordance with the components in COSO (Committee of Sponsoring Organizations). The data collection method used in preparing the thesis is the observation and interview method with the analysis method in the form of qualitative analysis. Suku Dinas Kebudayaan Kota Adminitrasi Jakarta Timur has an organizational structure that separates each staff's duties. From the results of observations and interviews using assessments measured by the five components of the internal control system for petty cash implemented by the Suku Dinas Kebudayaan Kota Adminitrasi Jakarta Timur, it is in accordance with the components of the internal control system.